The association between muscle strength and executive function in children and adolescents: Based on survey evidence in rural areas of China - Zeng, Qiang; Hu, Xin; Wang, Yujie (Frontiers in Psychology, 2023)
Background: In recent years, muscle strength in children and adolescents has continued to decline, especially in rural areas. Executive function as a higher function of the brain, is closely related to the future achievement of children and adolescents. For this reason, this study analyzed the correlation between muscle strength and executive function in children and adolescents in rural areas of China to better promote the development of muscle strength and executive function. Methods: Demographic factors, muscle strength, and executive function were tested in 1335 children and adolescents in rural China using a three-stage stratified whole-group sampling method. One-way ANOVA and chi-square test were used to compare the differences in executive function among children and adolescents with different muscle strengths. Multiple linear regression analysis and logistic regression analysis were used to analyze the association that exists between muscle strength and executive function. Results: When comparing the inconsistently, congruent, 1back, 2back, conversion, size parity, and cognitive flexibility response times of children and adolescents with different muscle strength indexes in rural China, the differences were statistically significant (F=46.592, 45.610, 10.809, 32.068, 24.095, 19.260, 11.501, p<0.001). Logistic regression analysis was performed using children and adolescents with muscle strength index>P80 as the control group. The results showed that the risk of 1back dysfunction was higher (OR=1.764, 95%CI:1.094,2.843) in children and adolescents with muscle strength indexP80, The muscle strength index